STRATEGI GURU PENDAMPING UNTUK MENDORONG INTERAKSI SOSIAL ANAK BERKEBUTUHAN KHUSUS DI KELAS REGULER - Pangayom, Arethusa Elyan; Septianingsih, Mia Aris; Rohmah, Asri Ainur; Minsih (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2024)
This research aims to find out how effective strategies are for accompanying teachers to encourage social interaction for children with special needs in regular classes. The aim of this research is also to increase the social interaction of children with special needs in regular classes and the involvement and social engagement of children with special needs in regular classrooms and to identify effective strategies used by supporting teachers. Data collection techniques through observation, interviews, documentation and data processing according to the research focus. Data validity testing was carried out through technical triangulation. Technical data analysis is carried out interactively. The informants involved were teachers accompanying slow learner students. The research results show that the strategies for encouraging social interaction for slow learner students are: 1) strategies for creating an inclusive environment, 2) collaboration strategies with related parties, especially parents, 3) strategies for differentiated teaching techniques to meet the individual needs of children in the class.